Prevalence and Determinants of Diabetic Foot Ulcers and Lower Extremity Amputations in Three Selected Tertiary Hospitals in Ghana - Ambrose Atosona; Christopher Larbie (Journal of Diabetes Research)
Background. The occurrence and complications of diabetes are increasing worldwide. This study examined the prevalence and determinants of diabetic foot ulcers and lower extremity amputations in three selected tertiary hospitals in Ghana. Methods. A cross-sectional multicenter study involving 100 subjects was carried out. Subjects were selected through simple random sampling from three selected tertiary hospitals in Ghana. A structured questionnaire was used to document information on sociodemographic, medical history, lifestyle, and physical characteristics of subjects. Foot ulcers and lower extremity amputations were also investigated. Total cholesterol, triglycerides, low-density lipoproteins, high-density lipoproteins, serum urea, serum creatinine, and estimated glomerular filtration rate of subjects were assessed. Data analysis was done using SPSS version 22. Results. The study revealed that 31% and 69% were males and females, respectively, with a mean age of 53.8±13.8 years. Among the patients, 11% had diabetic foot ulcers whilst 3% had lower extremity amputations. In the multivariate binary logistic regression analysis, previous history of foot ulcers (OR=40.4, 95% CI=5.5-299.9) and foot deformities (OR=14.4, 95% CI=1.3-161.2) were identified as independent predictors of diabetic foot ulcers. Foot deformity (p=0.043) and serum urea (p=0.002) were associated with diabetic lower extremity amputations in the univariate analysis. Conclusion. This study showed that the prevalences of diabetic foot ulcers and lower extremity amputations are high among diabetes patients. Foot deformities and previous history of foot ulcers are determinants of diabetic foot ulcers. Foot deformity and serum urea are associated with diabetic lower extremity amputations.